Change is an emotional state of mind: Behavioral responses to online petitions. (April 2018) - Koenig, Abby; McLaughlin, Bryan
Scholars are increasingly concerned about the rising level of negativity in social media sites. This negativity has found its way into sites that are supposedly intended for prosocial civic engagement. To examine how hostility impacts behavior in a user-generated, prosocial context, an experimental study was conducted using an online petition modeled after those posted to the websiteChange.org . This study examines whether negativity causes a contagion effect leading to more negativity and the different types of negativity that may occur. Results suggest that when users read negative-toned petitions, a contagion effect increases both anger and anxiety. However, our findings are not consistent with previous literature that argues anger leads to increased proactive behavior. Instead, we find that while anxiety leads to an increase in petition-related action, anger does not. These findings have important theoretical and practical implications for scholars and those looking to participate in social justice via online platforms.